Encompassing the Sacrifice: On the Narrative Construction of the Significant Past in the Sanskrit Mahābhārata - Hegarty, James M. M. (Acta Orientalia Vilnensia, 2006)
Cardiff UniversityThe Mahābhārata has, for millennia, been pivotal to processes of the construction of ideas of the cosmic and social past in South Asia. The text has also been of critical importance in establishing connections between Vedic and post-Vedic cosmic and social self-understandings. The key theoretical issue that underlies both these roles is of the nature of the relationship between narrative and the construction of forms of significant social knowledge in human social groups. The investigation of this relationship presents challenges to received conceptions of culture, history and structure within the academic disciplines of both Anthropology and History. Thisstudy explores the complex orientation to the past evident in the Sanskrit Mahābhārata. It also addresses the relationship between ideas of the past and issues of self-presentation in the text. I argue that the text constitutes itself as a ‘reflective’ or ‘theoretical’ technology in early South Asian religious discourse and that this strategy is intimately related to antecedent Vedic forms of knowledge and practice. I argue that this understanding of the text can shed light on wider processes in the formation and consolidation of Sanskritic knowledge systems in early South Asia. I also suggest that the example of the Mahābhārata can help refine more general theoretical orientations to the relationship between narrative, history and culture.